CALLUS GROWTH AND PLANT REGENERATION IN LAELIA SPECIOSA (ORCHIDACEAE) - Marcela Esmeralda Sarabia-Ochoa (Lankesteriana International Journal on Orchidology, 2010)
Laelia speciosa is an endangered epiphytic orchid, endemic to México. It is thought that the asexual reproduction in vitro could be one of the actions to counteract the massive extraction of individuals from their natural populations. The growth and differentiation of callus tissues derived from leaf explants of L. speciosa were investigated in Murashige and Skoog medium (MS) with 30 g l -1 sucrose and five concentrations (0.0, 0.25, 0.5, 1.0, and 2.5 g l -1 ) of naphthaleneacetic acid (NAA) with benzyladenine (BA) (0.0, 0.25, 0.5, 1.0, and 2.5 g l -1 ). Leaf explants from in vitro plantlets formed callus tissue on MS medium supplemented with 2.5 mg l -1 BA while mature leaves did not respond. Diameter of the callus tissues averaged 1.25 cm after eight weeks of culture. PLBs development was achieved on MS medium supplemented with 2.5 mg l -1 NAA and 1 mg l -1 BA. The formation of plantlets was successfully obtained in MS supplemented with 0.5 mg l -1 of NAA and 0.1 mg l -1 of gibberellic acid (GA 3 ). Obtained plantlets were successfully acclimatized in a greenhouse with a survival rate of 70%.